Perlindungan Hukum Terhadap Pekerja Berdasarkan Perjanjian Kerja Waktu Tertentu - Simarmata, Anggi Sri Haryati; Auliah Ambarwati; Reza Kautsar Kusumahpraja (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study explained that as time goes by (the era of globalization), problems in the field of employment are increasing, one of which is the clarity of legal protection for workers based on certain term work agreements. This research uses normative methodology through library research. Fixed-term work agreements and non-permanent workers in Indonesia still require legal protection regarding job status and security. Inappropriate conditions in an employment relationship between workers/laborers and employers are mainly related to the issue of fulfilling workers' rights within the scope of their work. The government has an important role in regulating labor regulations, especially as these regulations or norms serve as the basis for worker safety. Now, workers can know the laws that regulate the obligations between recipients and employers to prevent exploitation of workers and that there is a negotiation stage first before an agreement is made. It also regulates permits for termination of employment rights (PHK) which result in the end of the rights and obligations between the worker/employee and the employer. Therefore, it is natural for the government to regulate regulations, not only protecting workers' rights but also paying attention to the company's financial capacity by providing maximum regulations evenly.